Development Of Logical Thinking Of Future Teachers Of Mathematics Using The Methods Of Newton And Chebishev - Nafasov Ganisher Abdurashidovich; Davlatov O‘tkir Tagaevich; Eshmuratov Abdimannab (Genius Journals, 2024)
This article is devoted to the methodology of developing logical thinking of future mathematics teachers using the methods of Newton and Chebyshev, based on a related approach. Effective methods for developing logical competencies of future mathematics teachers are described
Keywords: monotone; convex; section; polynomial